The mother-child attachment bond before and after birth: The role of maternal perception of traumatic childbirth. (March 2020) - Smorti, Martina; Ponti, Lucia; Ghinassi, Simon; Rapisardi, Gherardo
Abstract: The quality of the mother-child attachment bond is a relevant factor for the psychosocial well-being of a child. However, some variables could affect this relationship, such as a perceived traumatic childbirth experience. The aim of this study was to explore the mediating role of the childbirth experience on the relationship between prenatal and postnatal attachment. A predictive study was conducted on 105 pregnant women aged 26 to 44 years. The data was collected at two different times: at week 31–32 of gestation (T1) and three months after childbirth (T2). The quality of maternal prenatal attachment has a significant and direct effect on postnatal mother-child attachment. Moreover, the quality of prenatal attachment represents a protective factor for the quality of childbirth experience, promoting a higher quality of postnatal attachment bond. Our results highlight the importance of supporting women throughout the perinatal period, starting from pregnancy to after childbirth. Highlights: The mother-child attachment bond affects the psychosocial well-being of a child. This emotional bond started during pregnancy, and it is named "prenatal attachment". The relationship between prenatal and postnatal attachment is not always direct. A perceived traumatic childbirth experience can influence this relationship.